ENHANCING THE COMPETITIVENESS OF INDONESIA'S HUMAN RESOURCES IN GLOBAL FREE TRADE: INTEGRATING PERFORMANCE MANAGEMENT AND SKILL DEVELOPMENT - Zulqarnain Zulqarnain; Rasty Yulia; Ana Susi Mulyani; Titis Nistia Sari; Fiesty Utami (Adisam Publisher, 2023)
In the pursuit of enhancing the competitiveness of Indonesia's human resources in the realm of global free trade, this research embarked on a comprehensive exploration of the integration of performance management and skill development. Through a mixed-methods approach, including surveys, interviews, literature review, and secondary data analysis, the study delved into the multifaceted dynamics of these strategies. The findings revealed a compelling interplay between performance management and skill development, highlighting the importance of aligning individual, team, and organizational goals with the broader economic agenda. While performance management exhibited strengths such as precise objective setting and effective reward systems, challenges concerning objectivity in performance appraisals were identified. Skill development emerged as a key focus, emphasizing the critical nature of digital literacy, foreign language proficiency, and cross-cultural communication skills in the global free trade landscape. The accessibility and availability of training programs were recognized as areas for improvement, along with the value of public-private partnerships in shaping skill development programs. This research contributes to Indonesia's competitiveness in global free trade by providing insights into integrating these strategies and emphasizing their alignment with national economic goals. Recommendations for policymakers and potential areas for future research and policy implementation are presented further to strengthen Indonesia's human resources on the global stage.